2015
DOI: 10.4103/0973-029x.157213
|View full text |Cite
|
Sign up to set email alerts
|

Benign lymphoepithelial cysts of parotid and submandibular glands in a HIV-positive patient

Abstract: Patients with human immunodeficiency virus (HIV) infection have been reported to have parotid swellings of various types such as diffuse infiltrative lymphocytosis syndrome, parotitis, intraparotid lymphadenopathy, benign lymphoepithelial cyst (BLEC), as well as salivary gland neoplasms such as adenoid cystic carcinoma, Kaposi sarcoma and lymphoma. LECs in the parotid gland are uncommon benign entities with increased incidence associated with HIV infection. We are presenting a case of 28-year-old HIV-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…The immunohistochemical studies on a LEC in HIV-infected patients have revealed HIV-1 p24 in residual dendritic cells of lymphoid follicles (follicular dendritic reticulum cells) and follicular and interfollicular macrophages [9,10,12]. Some authors have shown that the lymphoepithelial cyst contained a large amount of HIV-1 p24 and RNA copies, suggesting this lesion to be a reservoir of HIV [2,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunohistochemical studies on a LEC in HIV-infected patients have revealed HIV-1 p24 in residual dendritic cells of lymphoid follicles (follicular dendritic reticulum cells) and follicular and interfollicular macrophages [9,10,12]. Some authors have shown that the lymphoepithelial cyst contained a large amount of HIV-1 p24 and RNA copies, suggesting this lesion to be a reservoir of HIV [2,12].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our observations, we can only speculate that this lesion may be very rare, as it has been reported in humans. The incidence of the salivary LEC corresponded to less than 6% of the HIV-infected patients, but the exact incidence of the LEC in non-HIV patients is unknown [2,8].…”
Section: Discussionmentioning
confidence: 99%
“…3 Though differential diagnosis of salivary gland disease (SGD) in seropositive patients would include diffuse infiltrative lymphocytosis syndrome (DILS), parotitis, intraparotid lymphadenopathy, adenoid cystic carcinoma, Kaposi sarcoma, and lymphoma; their varied clinical, radiological, and microscopic features will differentiate them from BLECs. 6 Literature review has no mention of these entities in HIV negative patients.…”
Section: Discussionmentioning
confidence: 99%
“… 7 These cysts serve as a reservoir of HIV-1 p24 antigen and RNA copies that are about 1000-fold higher than plasma concentrations. 6 HIV has a predilection for lymphoid tissue and elevated concentrations of HIV can be found within these nodes. 8…”
Section: Discussionmentioning
confidence: 99%